Analisis Model Struktural Penyusunan Minat Berkunjung Kembali Masyarakat pada Event Maen Jaran di Sumbawa - Koko Hermanto; Tamara Exanti Olifia (Jurnal Matematika, 2025)
One of the advantages of Sumbawa Regency is its cultural diversity, the tradition of horse racing or commonly called the Maen Jaran Event (in Sumbawa language) is part of the culture and entertainment that has been preserved for centuries in Sumbawa. In efforts to preserve culture, especially traditional arts, it is increasingly difficult along with the development of the times and current globalization trends. Based on the results of observations there are several factors found in the Maen Jaran event there are several things that are less satisfied felt by visitors, namely the lack of facilities provided such as the lack of visitor stands, lack of trash cans, and parking spaces that are still relatively limited and the location where the Maen Jaran event is held far, visitors are less likely to leave because the location is quite far from their location point so that it will have an impact on the interest in returning when visitors get an uncomfortable experience or impression in assessing the quality of the event held. So to increase the interest in returning to the Maen Jaran event in Sumbawa, it is necessary to conduct a large analysis of visitor satisfaction, visitor experience, event quality and location on the interest in returning.Based on these problems, it is necessary to analyze the public’s intention to revisit the Maen Jaran event regarding visitor satisfaction, visitor experience, event quality, and location. In this study, a survey was conducted first and determined the research instrument used in collecting data, namely using a questionnaire with a non-probability sampling method, which must first determine the number of samples and distributed to 104 respondents. Furthermore, before conducting the SEM analysis, the instrument was tested for validity and reliability with a loading factor value that met the criteria (> 0.60). The method in this study was Structural Equation Modeling (SEM) with the Lisrel 8.80 software approach. Based on the results of the study, visitor satisfaction has a -28% relationship with the intention to revisit, visitor experience has an 84% relationship with the analyzed intention to revisit, event quality has a 5.1% relationship with the intention to revisit, while the location has a 24% relationship with the intention to revisit. The results of the study are expected to be a reference in decision making for Maen Jaran event organizers to maintain and increase public interest in visiting the Maen Jaran event.